Is law computable? : critical perspectives on law and artificial intelligence - Deakin, S. F. (Simon F.); Markou, Christopher (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"What does computable law mean for the autonomy, authority, and legitimacy of the legal system? Are we witnessing a shift from Rule of Law to a new Rule of Technology? Should we even build these things in the first place? This unique volume collects original papers by a group of leading international scholars to address some of the fascinating questions raised by the encroachment of Artificial Intelligence (AI) into more aspects of legal process, administration, and culture. Weighing near-term benefits against the longer-term, and potentially path-dependent, implications of replacing human legal authority with computational systems, this volume pushes back against the more uncritical accounts of AI in law and the eagerness of scholars, governments, and LegalTech developers, to overlook the more fundamental - and perhaps 'bigger picture' - ramifications of computable law. With contributions by Simon Deakin, Christopher Markou, Mireille Hildebrandt, Roger Brownsword, Sylvie Delacroix, Lyria Bennet Moses, Ryan Abbott, Jennifer Cobbe, Lily Hands, John Morison, Alex Sarch, and Dilan Thampapillai"--
From rule of law to legal singularity / Simon Deakin and Christopher Markou -- Ex machina Lex : exploring the limits of legal computability / Christopher Markou and Simon Deakin -- Code-driven law : freezing the future and scaling the past / Mireille Hildebrandt -- Towards a democratic singularity? algorithmic governmentality, the eradication of politics and the possibility of resistance / John Morison -- Legal singularity and the reflexivity of law / Jennifer Cobbe -- Artificial intelligence + legal singularity : the thin end of the wedge, the thick end of the wedge / Roger Brownsword -- Automated systems and the need for change / Sylvie Delacroix -- Punishing artificial intelligence : legal fiction or science fiction / Ryan Abbott and Alex Sarch -- Not a single singularity / Lyria Bennett Moses -- The law of contested concepts? Reflections on Copyright Law and the legal and technological singularities / Dilan Thampapillai -- Capacitas ex machina : are computerised assessments of mental capacity a 'red line' or benchmark for AI? / Christopher Markou and Lily Hands.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Data processing; Artificial intelligence -- Law and legislation; Law -- Computer network resources; Technology and law; Technological innovations -- Law and legislation; IT & Communications law; Electronic books